2014
DOI: 10.1371/journal.pone.0091081
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Profiling of Myeloid Immune Cell Subsets in Response to In Vitro Challenge with Porcine Circovirus 2b

Abstract: Compelling evidence suggests that the early interaction between porcine circovirus 2 (PCV-2) and the innate immune system is the key event in the pathogenesis of Post-Weaning Multisystemic Wasting Syndrome (PMWS). Furthermore, PCV2 has been detected in bone-marrow samples, potentially enabling an easy spread and reservoir for the virus. To assess the gene-expression differences induced by an in-vitro PCV2b infection in different three different myeloid innate immune cell subsets generated from the same animal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 70 publications
(88 reference statements)
1
17
0
Order By: Relevance
“…IL-8, a major neutrophil chemotactic factor, is an important participant in the migration of specific inflammatory cells from the peripheral blood to the inflammatory site during an innate immune response (Kunkel et al, 1991). In this study, we found that PCV2 activated IL-8 expression in PAMs, which is consistent with previous reports that IL-8 is upregulated both in vivo (Chae & Choi, 2011;Darwich et al, 2003a, b) and in vitro Mavrommatis et al, 2014). Expression levels of IL-8 vary with PCV2 infection status and rely on the efficiency of the innate immune response (Borghetti et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…IL-8, a major neutrophil chemotactic factor, is an important participant in the migration of specific inflammatory cells from the peripheral blood to the inflammatory site during an innate immune response (Kunkel et al, 1991). In this study, we found that PCV2 activated IL-8 expression in PAMs, which is consistent with previous reports that IL-8 is upregulated both in vivo (Chae & Choi, 2011;Darwich et al, 2003a, b) and in vitro Mavrommatis et al, 2014). Expression levels of IL-8 vary with PCV2 infection status and rely on the efficiency of the innate immune response (Borghetti et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported that PCV2 infection induces porcine IL-8 expression both in vivo and in vitro (Chae & Choi, 2011;Darwich et al, 2003;Li et al, 2013;Mavrommatis et al, 2014). To confirm these findings, IL-8 secretion from PCV2-infected PAMs was measured at the protein level by ELISA.…”
Section: Pcv2 Infection Triggers Il-8 Secretion In Pamsmentioning
confidence: 84%
See 1 more Smart Citation
“…During PCV2 infection, the expression levels of cellular genes are extensively modulated, and the resulting differentially expressed proteins are involved in the cytoskeleton, stress response, macromolecular biosynthesis, energy metabolism, ubiquitin-proteasome pathway, signal transduction, gene regulation, and immune response [38][39][40][41][42][43][44][45]. The virus-host interactions related to PCV2 proliferation are shown in Fig.…”
Section: Interactions Related To Pcv2 Propagationmentioning
confidence: 99%
“…The targets of PCV2 replication are mainly monocyte/macrophage and antigen-presenting cells (APCs), with several studies demonstrating the importance of the immune system in the pathogenesis of PMWS. For example, PMWS-affected pigs exhibit B-and T-cell depletion; diminishment of CD8 + , CD4 + CD8 + , and IgM + lymphocyte subsets; overexpression of IL-10 and IFN-c mRNA in the thymus and tonsils respectively; and decreased expression of IL-2 and IL-12p40 mRNA in the spleen (7,16,20,21,23). In addition, pigs affected by PMWS are more susceptible to secondary infection by bacteria (15).…”
mentioning
confidence: 99%